The Digital Pancreas: What AI Applications Are Revolutionizing Diabetes Management? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The global prevalence of diabetes mellitus presents one of the most significant public health challenges of the 21st century. The chronic, complex nature of ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine